The effect of heavy strength training on muscle adaptations and performance in elite nordic combined athletes - Kojedal, O.; Kvamme, B.; Losnegard, T.; Rønnestad, B. R.; Raastad, T. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Performance in Nordic combined is dependent on both endurance performance in cross country skiing and the ability to generate maximum power during take-off in ski jumping. Heavy strength training on leg muscles has the ability to improve power in leg extensors, but it is uncertain how a large volume of endurance training may influence this adaptation. Furthermore, strength training of upper body muscles may also improve performance in cross country skiing (Hoff et al., 2002). However, the effect of heavy strength training has not been investigated in Nordic combined athletes. Thus, the aim of this study was to investigate the effect of adding heavy strength training to normal training in elite Nordic combined athletes. Methods 17 male Nordic combined athletes (16-26 yrs, VO2max: 66.2±1.2 ml·kg-1·min-1) were assigned to a strength training group (STR, n=8) and a control group (CON, n=9). STR performed strength training twice a week, for 12 weeks with 3-5 x 10-3 repetition maximum (RM) training loads in two exercises for upper-body (seated pull-down and standing double poling) and one exercise for the lower-body (deep squat) as a supplement to their regular training. CON maintained regular training without heavy strength training. Measurements of muscle thickness, 1RM, roller ski performance (7.5 km time trial), work economy and VO2max during treadmill roller skiing and vertical jump-height were performed before and after the training intervention. Results STR increased muscle thickness of m. vastus lateralis (7.1±3.0%) while no change was observed in CON (-2.2±2.5%). STR improved 1RM in both seated pull-down and deep squat (23±6% and 12±4% respectively), while no change was observed in CON. Vertical jump-height improved in STR (8.8±4.9%), while no change was observed in CON. The change in relative strength in deep squat was correlated with changes in vertical jump-height (r=0.59). Maximal aerobic power in ski skating, time-trial roller ski performance, skiing economy, and body weight remained unchanged from before to after intervention in both groups. Discussion As expected, the 12-week period of heavy strength training improved 1RM deep squat and increased vertical jumping height (McBride et al., 2002). On the other hand, we did not observe any improvements in maximal aerobic power or working economy during ski skating. The increase in muscle thickness did not lead to a subsequent increase in body weight. Altogether; strength training may improve total performance in Nordic combined by improving the athletes` ability to mobilize maximal power during ski jumping without negatively affecting cross country skiing performance. References Hoff, J., Gran, A., & Helgerud, J. (2002). Scand.J.Med.Sci.Sports. 12, 288-295. McBride, J. M., Triplett-McBride, T., Davie, A., & Newton, R. U. (2002). J.Strength.Cond.Res., 16, 75-82.